A full-path phasing technique based on the far-field interference fringe for tiled-aperture coherent beam combining. (31st August 2018) - Peng, Chun; Liu, Renqi; Wu, Weishu; Li, Wenqi; Liang, Xiaoyan; Li, Ruxin
Abstract: We propose a new phase error measurement and control technique based on the far-field interference fringe (FFIF) for a coherent beam combined with a tiled-aperture design. By using this method, the phase error can be directly measured at the focal plane, enabling a visual monitor of full-path measurement without introducing extra optical elements before focusing. The analytical expression of the relation between far-field distributions and phase errors is derived, which gives a theory guidance by the phase extraction from the FFIF. A proof of the principle experiment is demonstrated and a residual phase jitter of 0.157 rad (approximately 1/40 λ ) is achieved, which is adequate for a coherent beam combined with femtosecond pulses.